Comparative identification and differential expression pattern of amino acid permease genes in Elaeis guineensis. Issue 1 (1st January 2019) - Li, Jia; Cao, Xianmei; Liu, Yanju; Lei, Xintao; Fang, Zhongming
Abstract: Elaeis guineensis is a tropical crop with high oil content, and the nutritional value of oil is very high. Amino acids not only affect the growth and development of plants but also act as intermediate metabolites of oils, which determine the final quality of oils. In this study, eleven amino acid permease genes ( EgAAPs ) in E. guineensis were identified from the amino acid transporter family. Real-time PCR results showed that seven EgAAPs ( EgAAP1, EgAAP2, EgAAP3, EgAAP4, EgAAP6 EgAAP9, and EgAAP10 ) played an important role in vegetative growth because of their higher expression levels in roots and leaves, but EgAAP5, EgAAP7, EgAAP8 and EgAAP11 were also important for their higher expression levels in flowers or fruits. E. guineensis seedlings were treated with 20% PEG-6000 and 4 °C to induce drought stress and cold stress, respectively. The expression of six EgAAPs ( EgAAP1, EgAAP2, EgAAP4, EgAAP6, EgAAP8 and EgAAP11 ) was decreased in both roots and leaves during cold treatment, and only the expression of EgAAP5 was increased in both roots and leaves after 6 h of cold treatment. The expression of six EgAAPs ( EgAAP2, EgAAP4, EgAAP7, EgAAP8, EgAAP10 and EgAAP11 ) was decreased in roots but increased in leaves under PEG treatment, indicating an opposite pattern of expression levels of these EgAAPs in roots and leaves. However, only EgAAP5 had a similar pattern of expression levels between roots and leaves under PEG treatment. The findings provide information on how EgAAPs in E. guineensis are regulated during growth and development, and under various environmental stresses.